The influence of romantic partners on male risk-taking. (May 2020) - Silva, Karol; Chein, Jason; Steinberg, Laurence
Studies show that young men's tendency to take risks may be exacerbated or attenuated in different social contexts. Despite widespread evidence that social context influences young men's risk-taking, few studies have examined the impact of romantic partners on risky decision-making. The present study examined risk-taking among young men in relationships with women ( n = 134, ages 18–24) randomly assigned to be tested alone ( n = 47), in the presence of their romantic partner ( n = 44), or in the presence of an attractive female stranger ( n = 43). The presence of a romantic partner diminished young men's tendency to take risks. Findings demonstrate that a dampening effect on risk-taking is attributable to the romantic partner's presence and not merely due to knowledge of being in a relationship.